Efficiency and productivity performance of zakat funds in Algeria - Djaghballou, Chams-Eddine; Djaghballou, Mohamed; Larbani, Moussa; Mohamad, Azhar (Emerald, 2018)
Purpose The purpose of this study is to examine the efficiency and productivity performance of zakat funds managed by Directorates of Religious Affairs and Endowments (DRAE) in Algeria.